Clinical Presentation Of Reitet's Syndrome Among Iraqi Patients - Salman, Sami; AI-Najar, Ahmad A. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: To shed some light on the clinical features of patients with Reiter's syndrome.Methods: Reiter's syndrome in 50 patients (38 males and 12 females) was reported in a prospective study. All patients were subjected to detailed history, full clinical assessment and a slitlamp eye examination by an Ophthalmologist. A Dermatologist opinion was sought when needed and thorough laboratory and radiological investigations were made for all patients.Results: Reiter's syndrome was post-dysnteric in 44 (88%) of patients and post-venereal in 6 (12%) patients. Its clinical features are similar to other series. Arthritis was noted in allpatients, diarrhea in 44 (88%), eye lesions in 40 (80%) and mucocutaneous lesions in 37 (74%) patients but significant differences were noted between our study and others with respect to sex ratio, lower back pain, urethritis, oral ulcer, circulate balanitis. Tissue typing for HLA-B27 was positive in 72% of our patients.Conclusions: Reiter's syndrome is not rare in Iraq as previously thought. Physicians need to be more aware of its existence in young adult men who develop arthritis following dysentery.